The Role of Vascular Endothelial Growth Factor Receptor-1 Signaling in the Recovery from Ischemia - Amano, Hideki (PLoS One, 2015)
Vascular endothelial growth factor (VEGF) is one of the most potent angiogenesis stimulators. VEGF binds to VEGF receptor 1 (VEGFR1), inducing angiogenesis through the receptor’s tyrosine kinase domain (TK), but the mechanism is not well understood. We investigated the role of VEGFR1 tyrosine kinase signaling in angiogenesis using the ischemic hind limb model. Relative to control mice, blood flow recovery was significantly impaired in mice treated with VEGFA-neutralizing antibody. VEGFR1 tyrosine kinase knockout mice (TK(-/-)) had delayed blood flow recovery from ischemia and impaired angiogenesis, and this phenotype was unaffected by treatment with a VEGFR2 inhibitor. Compared to wild type mice (WT), TK(-/-) mice had no change in the plasma level of VEGF, but the plasma levels of stromal-derived cell factor 1 (SDF-1) and stem cell factor, as well as the bone marrow (BM) level of pro-matrix metalloproteinase-9 (pro-MMP-9), were significantly reduced. The recruitment of cells expressing VEGFR1 and C-X-C chemokine receptor type 4 (CXCR4) into peripheral blood and ischemic muscles was also suppressed. Furthermore, WT transplanted with TK(-/-) BM significantly impaired blood flow recovery more than WT transplanted with WT BM. These results suggest that VEGFR1-TK signaling facilitates angiogenesis by recruiting CXCR4(+)VEGFR1(+) cells from BM.